Polymorphic Distributed Energy Management for Low-Carbon Port Microgrid With Carbon Capture and Carbon Storage Devices - Shan, Qihe; Song, Jing; Xu, Qi; Xiao, Geyang; Yu, Feifei (Frontiers in Energy Research, 2022)
In order to reduce the carbon emission of the port and build a green port, a polymorphic distributed energy management method for the low carbon port microgrid with carbon capture and carbon storage device is proposed. Firstly, this paper presents a low carbon port microgrid in a polymorphic network environment to realize the information interaction among energy subjects in different modes and improve network communication performance among port power generation device, main grid, carbon capture and carbon storage device. Secondly, the energy management model of low-carbon port microgrid is constructed considering the additional carbon capture device and carbon storage device in the port. Then, based on the multi-agent consensus algorithm, a distributed energy management method is proposed, which is respectively oriented to the grid-connected operation mode, island operation mode and switching operation mode of the port microgrid, so as to achieve the economic, low carbon and reliable operation of the port microgrid. Finally, the simulation results of Matlab verify the effectiveness of the proposed method.